2023
DOI: 10.3390/su15021620
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Attitude towards Waste Separation and Recovery on Campus

Abstract: As large communities, the efficiency and effectiveness of waste management on university campuses are of concern. This study aims to verify the variable relationship, influence path, and regulating factors of college students’ attitudes and behavior toward waste separation. A questionnaire survey was conducted at Henan Institute of Science and Technology, China, with 1300 respondents, among which 1213 questionnaires were valid. The SPSS software v23.0 was used to carry out the statistical analysis of the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The findings of this study correspond to the findings of a study by (Rahmatika Dewi et al, 2022) which shows that behavior towards CE is categorized as high. This finding also supports the study by Qu et al, (2023) and Deda et al, (2022) which shows that the attitude of university students affects their behavior. This means that students who have a positive attitude towards product recovery and optimization, as recommended by Deda et al, (2022), tend to adopt behaviors that support the circular economy concept, as suggested by Qu et al, (2023).…”
Section: University Students Behavior Towards Circular Economysupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of this study correspond to the findings of a study by (Rahmatika Dewi et al, 2022) which shows that behavior towards CE is categorized as high. This finding also supports the study by Qu et al, (2023) and Deda et al, (2022) which shows that the attitude of university students affects their behavior. This means that students who have a positive attitude towards product recovery and optimization, as recommended by Deda et al, (2022), tend to adopt behaviors that support the circular economy concept, as suggested by Qu et al, (2023).…”
Section: University Students Behavior Towards Circular Economysupporting
confidence: 91%
“…The conclusion of this study emphasizes the importance of providing comprehensive information about renewable products to influence consumer attitudes towards the circular economy and, in turn, support efforts to achieve the SDGs. Qu et al (2023) looked at how college students at the Henan Institute of Science and Technology in China felt and behaved about garbage segregation. According to a questionnaire study of 1213 respondents, first-year students behaved more positively toward trash separation than second-and third-year students.…”
Section: Literature Review University Students Attitude and Behavior ...mentioning
confidence: 99%
“…In another study, Chao and colleagues (2023) demonstrated that intrinsic motivation, interpersonal altruism, and place attachment positively predicted undergraduates' recycling behavior. Having knowledge about environmental issues (e.g., Baba-Nalikant et al, 2023;Levy & Marans, 2012;Liao & Li, 2019;Qu et al, 2023), environmental concern (e.g., Chao et al, 2023;Hamilton & Rane, 2022;Qu et al, 2023), the existence of subjective norms regarding ecological conservation (e.g., Liao & Li, 2019), moral obligation (e.g., Largo-Wright et al, 2012), membership in ecological organizations (e.g., Helferty & Clarke, 2009), the inclusion of environmental issues to lectures (e.g., Pizmony- Levy & Michel, 2018), and prioritizing biospheric values (e.g., Hamilton & Rane, 2022) are the other predictors of on-campus pro-environmental behaviors.…”
Section: On-campus Pro-environmental Behaviorsmentioning
confidence: 99%
“…Therefore, efficient solid waste management structures are crucial for the sustainability of university campuses and their surrounding communities. Solid waste is a major contributor to the overall waste generation by universities globally, highlighting the need for a detailed understanding of existing waste management practices, challenges, programs, plans, systems, and policies (Qu et al, 2023). In line with sustainability principles, there is a growing interest in analyzing and evaluating resource recovery and recycling options for solid waste management in higher educational institutions (Smyth et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, municipalities face multiple solid waste related problems that surpass their capabilities, due to the lack of structure, financial resources, and system complexity (Guerrero et al., 2013). The situation is worse in developing countries, where poor solid waste management practices cause major environmental problems, such as pollution of water bodies, blockage of canals and drainage, and spread of diseases (Ayeleru et al., 2023; Ferronato & Torretta, 2019; Qu et al., 2023). A critical and difficult challenge in solid waste management is the quantity, complexity, and composition of waste generated by academic institutions (Owojori et al., 2020).…”
Section: Introductionmentioning
confidence: 99%